Oleanan Derivate Compounds From Melochia umbellata (Houtt) Stapf var. Degrabrata K Bark And Their Bioactivity - Usman, Usman; Soekamto, Nunuk H.; Usman, Hanapi; Ahmad, Ahyar (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2014)
Oleanan derivated 3-acetyl-12-oleanen-28-oat has been isolated from the n-hexane fraction of M. umbellata(Houtt) Stapf var. degrabrata K. bark. The molecular structure were determined by IR spectroscopy, 1D and 2DNMR (1H, 13C, DEPT, COSY, HMQC and HMBC) data analysis. Bioactivity tested results indicated that thecompound was toxic to A. salina with LC50 value was 361.93 mg/mL. At the concentration of 1000 mg/mL 3acetyl-12-oleanen-28-oat gave the highest inhibition to bacteria B. subtilis and the fungus C. albicans with the inhibited zone diameter was 15.8 mm and 15.2 mm, res.